Educational Impact of a Pulsatile Human Cadaver Circulation Model for Endovascular Training. (October 2019) - Nesbitt, Craig I.; Tingle, Samual J.; Williams, Robin; McCaslin, James E.; Searle, Roger; Mafeld, Sebastian; Stansby, Gerard P.
Abstract : Objectives: The face and construct validity of a novel pulsatile human cadaver model (PHCM) was recently demonstrated for endovascular training. This study aimed to assess the model's educational impact. Methods: Twenty-four endovascular novices were recruited and split into two equal training groups: PHCM and virtual reality simulator (VRS). Each candidate performed eight consecutive training attempts of endovascular renal artery catheterisation on their designated model, and a final crossover attempt on the alternate model. Performances were video recorded and scored using a validated scoring tool by two independent endovascular experts, blinded to the candidate's identity and attempt number. Each participant was given a task specific checklist score (TSC), global rating score (GRS), and overall procedure score (OPS). Results: In the PHCM group average OPS improved gradually from 19.42 (TSC 8.58, GRS 10.83) to 39.50 (TSC 15.00, GRS 24.5) over eight attempts ( p < .0005). In the VRS group OPS improved from 20.54 (TSC 10.29, GRS 10.25) to 36.04 (TSC 14.21, GRS 21.88) between the first and eighth attempts ( p < .0005), with limited improvement after the second attempt. PHCM training significantly improved OPS on their VRS crossover attempt ( p ≤ .0001), achieving a similar OPS to candidates who had completed VRS training ( p = .398). VRS training significantly improved OPS on PHCM ( p < 0.05); however, OPS was significantly worse than candidates who had completed PHCM training ( p ≤ .001). Conclusions: PHCM training has a longer learning curve, with gradual improvement, reflecting the enhanced difficulty of a more realistic model. These results support the use of PHCM preceded by VRS training, prior to performing endovascular surgery on patients.